AB1121 The Forgotten Joint Score, A New Questionnaire to Evaluate Patient's Perception of Total Knee and Hip Arthroplasty in Patients with Established Rheumatoid Arthritis. (10th June 2014) - Azzi, E.; Thienpont, E.; Avaux, M.; Houssiau, F.A.; Durez, P.
Abstract : Background: The "Forgotten Joint" score has been recently developed as a patient reported outcome in hip and/or knee total joint arthroplasty (TJA). This questionnaire analyses patient's perception to forget the artificial joint in everyday life. In patient with osteoarthritis, this new score showed a low ceiling effect, a high internal consistency and could discriminate patient groups with different outcomes. Since TJA is frequently performed and effective in severe rheumatoid arthritis (RA), the purpose of this study is to test the "Forgotten Joint" score (FJS-12) in this population. Methods: Between June and September 2013, RA patients who underwent TJA more than one year ago were asked to fill in the FJS-12 questionnaire during their routine visit. Data collected included the ACR/EULAR core set parameters, a pain VAS scale for the TJA, HAQ-DI, SF36 and HAD questionnaires in French. The range of the FJS-12 is 0 to 100, high scores indicate good outcome, that is, a high degree of forgetting the joint. Results: 49 patients (46 women and 3 men) with 74 TJA (48 TKA, 26 THA) were included The mean patient age was 54.4 years (range 32-75 years) with a mean disease duration of 15.3 years, a mean DAS28-CRP of 2.95, a mean HAQ-DI of 1.38, a mean mental health SF36 score of 48.4 and a mean physical health SF36 score of 36.6. The mean follow-up of the prothesis was 9.4 years. The mean FJS-12 in all TJA was 75.6 with a score of 72.9 for TKA and 80.8 for THA. The average pain VAS score was 14.78 (0-100). Conclusions: The Forgotten Joint score is an useful questionnaire to evaluate joint arthroplasty in RA. Patients with established RA were highly satisfied from their arthroplasty and yielded a high ability to forget their artificial joint despite a severe and longlasting disease. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4496